Carbon dynamics in soil aggregates with different types of land uses in Monte Tláloc, State of Mexico - Barrales-Brito, Edgar; Paz-Pellat, Fernando; Etchevers-Barra, Jorge Dionisio; Hidalgo-Moreno, Claudia; Velázquez-Rodríguez, Alma (REVISTA TERRA LATINOAMERICANA, 2020)
Changes in land use influence the carbon dynamics in ecosystems given these modify the soil structure and increase the mineralization rates of organic matter. In this study, we evaluated the effect of soil use, depth and size of aggregates on carbon (C) and soil respiration (CO2) content emitted by the mineralization of C in soils with different land uses (forestry, acahual, grassland and agricultural) in Mount Tláloc. Soil C was higher in forest ecosystems (over 100 g C kg-1 of soil) than in soils with agricultural, acahual and grassland use with 20, 30 and 50 g C kg-1 of soil, respectively. In sites with forest land use, mean weighted diameter values were larger than 1.5 mm and a greater percentage of macroaggregates (>2 mm; >25%) was found, which indicated a better soil structure in the first 30 cm depth with respect to the site with agricultural use, where microaggregates were predominant (< 0.5 mm) with percentages higher than 50%, and a lower amount of C (less than 10 g C kg-1 of soil) was detected, as well as a higher amount of CO2 emitted by respiration (greater than 40 g CO2 kg-1 of soil). The soil structure stability influenced the dynamics of C, given that a better soil structure presented a higher content of C and a decrease of CO2 emissions of the soil.